Papillon–Lefèvre syndrome: a report of two cases - S. PATEL & L. E. DAVIDSON (Paediatric Dentistry, 2004)
Papillon–Lefèvre syndrome is a rare disease characterized by skin lesions caused by palmar-plantar hyperkeratosis, and severe periodontal destruction involving both the primary and permanent dentitions.